Sharḥ-i akhbār u abyāt u amthāl-i ʿArabi-yi Kalīla wa Dimna : Dū sharḥ az Faḍlallāh ʿUthmān b. Muḥammad al-Isfizārī wa muʾallifī nā shinākhta - Īmānī, Bihrūz, (Miras Maktoob, ISBN: 9789004365452., 2019)
Throughout history, Indian culture has had the interest of the Persians. At the time of the Sasanids (3rd-7th cent. CE) for instance, Sanskrit works on astronomy were translated into Pehlavi. Centuries later, in the early ʿAbbāsid period, a number of astronomers with a Persian background used information from these very same sources in writing their own books in Arabic. Besides scientific works, spiritual and ethical texts were also translated. An example is the famous collection of animal fables called Kalila and Dimna , which go back to the lost Sanskrit Pañcatantra . An equally lost Middle Persian translation of this work was rendered into Arabic several times, but the translation by Ibn al-Muqaffaʿ (d. ca. 139/757) proved most influential and formed the basis of the famous Persian translation by Naṣrallāh Munshī (6th/12th cent.). On this latter translation, two Persian commentaries from the 7th/13th century survive. A critical edition of both is offered in this volume.